Tropicamide has limited clinical effect on cycloplegia and mydriasis when combined with cyclopentolate and phenylephrine - Sherman, Alain E.; Shaw, Melissa M.; Ralay-Ranaivo, Hantamalala; Rahmani, Bahram (Journal of AAPOS, 2019)
To examine the cycloplegic and mydriatic effect of tropicamide omission from a common pediatric eye drop combination. Consecutive children examined at the Ann & Robert H. Lurie Children's Hospital of Chicago from June 8, 2017 to September 6, 2017 were enrolled prospectively. Tropicamide, cyclopentolate, and phenylephrine (TCP) was instilled in one eye; cyclopentolate and phenylephrine (CP), in the other. Spherical equivalent, maximum pupil size, and pupillary constriction in response to photostimulation were measured before and 30 minutes after instillation using an autorefractor and pupillometer. Iris pigmentation was examined as a between-subjects variable. A total of 75 children 4-11 years of age were included. Mean differences in spherical equivalent between TCP and CP were not statistically significant (P = 0.95). Significant interactions between eye drop regimen and iris pigmentation were observed for pupil size (P = 0.001) and constriction percentage (P = 0.02). Among only patients with dark irides, TCP yielded slightly larger pupils (7.70 vs 7.31 mm [P < 0.001]) that were less responsive to light (5.75% vs 8.07% [P = 0.002]). All pupils dilated to ≥6.0 mm, with equivalent proportions achieving ≥7.0 mm for TCP and CP (P = 0.18). TCP and CP elicited equivalent cycloplegic effects. Mydriatic differences between the regimens, although statistically significant in dark irides, were of limited clinical magnitude, and all pupils achieved sufficient dilation for funduscopy.